A Prospective, Randomized, Comparative Study of Topical Minocycline Gel 4% with Topical Clindamycin Phosphate Gel 1% in Indian Patients with Acne Vulgaris - Bela Shah; Deval Mistry; Nelry Gonsalves; Presha Vasani; Dhiraj Dhoot; Hanmant Barkate (MDPI AG, 2023)
Acne vulgaris is characterized by inflammatory and non-inflammatory skin lesions with a high prevalence among adolescents in India. Not enough studies are reported on the use of topical antibiotics for the management of acne in the Indian population. The proposed study aims to compare the efficacy and safety of topical minocycline gel 4% with topical clindamycin gel 1% in the Indian population. A randomized, open-label, double-arm study was planned at two centers in India. One hundred patients were enrolled and randomized equally to two treatment arms. The drugs were applied once daily, preferably at the same time each day. The number of inflammatory and non-inflammatory lesions, as well as the investigator's global assessment (IGA), were obtained at the baseline and on weeks 3, 6, 9, and 12. The change in these parameters from baseline to week 12 was compared between the two treatment arms. A tolerability assessment was also performed on selected parameters. The age of patients ranged between 14 and 31 years, with female preponderance in each arm. On week 12, the percent change in inflammatory and non-inflammatory lesions in the minocycline 4% arm was significantly higher than in the clindamycin 1% arm (p < 0.0001). The IGA treatment success was significantly higher in the minocycline arm compared to the clindamycin arm on weeks 9 and 12, with p-values of 0.001 and 0.015, respectively. Tolerability assessment revealed significantly improved parameter performance in the minocycline arm compared to the clindamycin arm. On subgroup analysis, in adolescents, minocycline was found to be more efficacious than clindamycin. The comparative assessment resulted in a significantly improved performance of minocycline gel 4% compared to clindamycin gel 1% in the Indian population, thus making it a preferred choice for the treatment of moderate-to-severe acne in India.